THE DEVELOPMENT OF THE ISLAMIC BANKING IN THE CIS COUNTRIES: EXISTING BARRIERS AND EXPECTED OPPORTUNITIES - Muhamedov Bahtinur Bahtiyor ugli; Iroda Norova Rustambek qizi (Scholar Express Journals, 2021)
This article is devoted to a clear reflection and analysis of the factors that necessitate the introduction of Islamic banking as an alternative to the traditional banking system in overcoming the main problem indicators of the current situation of monetary policy in the CIS countries. The study examines the important steps for the introduction of Islamic banking in the countries of the region, attitudes towards them, as well as the obstacles encountered and their possible solutions. Almost all statistical tables and diagrams reflected in the article were prepared by the author based on the sources of international financial institutions and rating agencies.
Keywords: liquidity; monetary policy; Islamic finance; IDB